Perancangan Sistem Informasi Peralatan Kesehatan Dengan Metode Waterfall - Andi Taufik; Ade Christian; Taufik Asra (Universitas Bina Sarana Informatika, 2019)
The development of information technology is very rapid. Computers are tools that are created to facilitate human work for all fields. It cannot be separated from the business field, if it cannot compete by using technological advances, the company will be left behind. At present there are still companies selling medical devices where the sales system still uses manual systems. The manual system has problems such as errors in recording, inaccuracy of reports made and delays in finding the data needed. The design of a computerized information system is the best solution to solve the problems that exist in this company. The system is made using the waterfall method to be easy in the process, and with a computerized system can be achieved an activity that is effective and efficient and accurate. Because it's easier in data processing and faster in presenting the information.